Smoking and Substance Abuse among Medical Students in Iran - Ghasemi, Hadi; Jadidfard, Mohammad pooyan; Asgharian, Mehrdad (Journal of Dental School, 2022)
Objectives Drug abuse is a critical health problem in human societies. This study aimed to evaluate the prevalence and determinants of drug abuse among students in a medical university in Iran. Methods This cross-sectional study was performed in 2016 on a convenient sample of 800 undergraduate students in a medical university in Tehran, Iran. Data were gathered by means of a self-administered questionnaire inquiring the students’ age, gender, marital status, home city, living status, smoking, and drug abuse including history, frequency and type. Statistical analyses were performed by the Chi-square test and logistic regression models. Results The mean age of the respondents was 23.5 years; 67% were males, and 70% were single. Totally, 15% of the students reported cigarette smoking and ≤ 6% used other drugs. The frequency of substance abuse by male students was significantly higher than that by female students (P<0.01). Alcohol consumption was reported by 7% of the students, and had a significantly higher frequency among females (P=0.02). Older students, those spending their free time alone, and those without a job had higher frequency of drug abuse (P≤0.001). Conclusion Prevalence of drug abuse was low among medical students evaluated in this study, and most of them reported no smoking. Some demographic and lifestyle factors may predispose students to smoking and drug abuse. Provision of preventive programs including surveillance, consultation and treatment will help university students avoid such risky behaviors.